Nutritional benefits - WRENmedia (Technical Centre for Agricultural and Rural Cooperation, 2008)
Judith Kimiywe, a nutritionist from Kenyatta University, believes that traditional vegetables are an ideal solution for the micronutrient deficiencies that are a common cause of poor health. Leafy vegetables like spider weed, sweet potato and cassava leaves, and other food plants picked from the wild are high in vitamin A, iron, zinc and iodine. Mixing different types of vegetables helps to achieve a good balance of nutrients, which protect the body from many kinds of illness and can help to manage conditions such as diabetes, HIV and TB.